DESIGN AND DEVELOPMENT OF MSMES JERKY KALE PRODUCTS IN CANDIHARJO VILLAGE - Rezania, Vanda; Hayuningrat, Dewi Asmara Cahyani; Fitriansyah, Muhammad Aditya; Ubeidillah, Himawan Noer Alfan; Zahira, Anggita Zam; Nailirrohmah (Journal of Social Comunity Services, 2025)
Objective: This research aims to develop processed kale products into snacks with high economic value in the form of kale jerky as an effort to increase the added value of local commodities and strengthen the competitiveness of MSMEs in Candiharjo Village. Method: The implementation method includes observation of local potential, deepening the production process, socializing market strategies, developing packaging and product design, as well as active promotion through social media and digital content creation. Results: The results show that the design and development of DEKACAN (Dendeng Kangkung Candiharjo) products includes comprehensive stages, ranging from product rebranding, label creation, and visual identity (packaging, posters, x-banners), to online marketing strategies. The primary packaging used in the form of a transparent stand-up pouch with an attractive label sticker design has been proven to be able to increase consumer interest in products. In addition, the use of social media, especially Instagram Business, is considered effective for expanding market reach because it offers features that support visual and interactive promotions at a low cost. Novelty: The novelty of this research lies in the transformation of kale into a jerky product that is not yet common in the market, as well as the combination of visual design strategies and digital marketing based on local potential that has a direct impact on the growth of MSMEs. This approach also shows how traditional products can be developed into modern products that are able to keep up with trends and increase market attractiveness in a sustainable manner.